2022
DOI: 10.1172/jci163614
|View full text |Cite
|
Sign up to set email alerts
|

Protein vaccine NVX-CoV2373 elicits functional T cell immunity

Abstract: The SARS-CoV-2 vaccine NVX-CoV2373 is a protein-based vaccine that might circumvent the difficulties in distributing mRNA vaccines to regions with limited access to cold-chain and refrigeration. However, the NVX-CoV2373–induced T cell and antibody responses remain poorly understood. In this issue of the JCI , Moderbacher et al. characterized SARS-CoV-2–specific CD4 + and CD8 + T cell responses elicited by one or two doses of NVX-CoV2373 in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
2
2
0
Order By: Relevance
“…SARS-CoV-2 mRNA vaccines can induce robust antigen-specific TFH responses in both peripheral blood and lymph nodes and maintained for 6 months (14,15,39). Similarly, our study found that CoronaVac vaccine efficiently elicited spike-specific, IFN-γ/IL-2 producing CD4 + T cells and cTFH cells necessary for the anti-viral and antibody response (26,(40)(41)(42). And the expanded spike-specific cTFH cells were biased to the proinflammatory cTFH17 subsets post the 2 nd and 3 rd dose of CoronaVac, which was also found after SARS-CoV-2 infection (43,44).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…SARS-CoV-2 mRNA vaccines can induce robust antigen-specific TFH responses in both peripheral blood and lymph nodes and maintained for 6 months (14,15,39). Similarly, our study found that CoronaVac vaccine efficiently elicited spike-specific, IFN-γ/IL-2 producing CD4 + T cells and cTFH cells necessary for the anti-viral and antibody response (26,(40)(41)(42). And the expanded spike-specific cTFH cells were biased to the proinflammatory cTFH17 subsets post the 2 nd and 3 rd dose of CoronaVac, which was also found after SARS-CoV-2 infection (43,44).…”
Section: Discussionsupporting
confidence: 70%
“…Sequential COVID-19 vaccinations with diverse vaccine platforms can effectively induce robust adaptive immune responses that provide protection against severe complications caused by SARS-CoV-2 and its subvariants (26,40,49). While the magnitudes of spikespecific and variant-specific antibody and T cell responses are mostly comparable between BNT162b2 and mRNA-1273, and higher than those induced by Ad26.COV2.S and NVX-CoV2373, direct comparison studies on comprehensive clinical and immunological parameters between inactivated COVID-19 vaccines such as CoronaVac and other vaccine platforms are limited (50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 mRNA vaccines can induce robust antigen-specific Tfh responses in both peripheral blood and lymph nodes that are maintained for 6 months ( 8 , 14 , 15 ). Similarly, our study found that CoronaVac vaccine efficiently elicited spike-specific IFN-γ/IL-2–producing CD4 + T cells and cTfh cells necessary for the antiviral and antibody response ( 24 , 37 39 ). The expanded spike-specific cTfh cells were biased toward the proinflammatory cTfh17 subsets after the second and third dose of CoronaVac, which was also found after SARS-CoV-2 infection ( 40 , 41 ).…”
Section: Discussionsupporting
confidence: 70%
“…Sequential COVID-19 vaccinations with diverse vaccine platforms can effectively induce robust adaptive immune responses that provide protection against severe complications caused by SARS-CoV-2 and its subvariants (24,37,47). Although the magnitudes of spike-specific and variant-specific antibody and T cell responses are mostly comparable between BNT162b2 and mRNA-1273, and higher than those induced by Ad26.COV2.S and NVX-CoV2373, direct comparison studies on comprehensive clinical and immunological parameters between inactivated COVID-19 vaccines such as CoronaVac and other vaccine platforms are limited (48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%